A phase II trial of the FGFR inhibitor pemigatinib in patients with metastatic esophageal–gastric junction/gastric cancer trastuzumab resistant: the FiGhTeR trial. (July 2020) - Merz, Valeria; Zecchetto, Camilla; Simionato, Francesca; Cavaliere, Alessandro; Casalino, Simona; Pavarana, Michele; Giacopuzzi, Simone; Bencivenga, Maria; Tomezzoli, Anna; Santoro, Raffaela; Fedele, Vita; Contarelli, Serena; et al.
Background: Prognosis of patients affected by metastatic esophageal–gastric junction (EGJ) or gastric cancer (GC) remains dismal. Trastuzumab, an anti-HER2 monoclonal antibody, is the only targeted agent approved for the first-line treatment of patients with HER2-overexpressing advanced EGJ or GC in combination with chemotherapy. However, patients invariably become resistant during this treatment. We recently identified the overexpression of fibroblast growth factor (FGF) receptor 3 (FGFR3) as a molecular mechanism responsible for trastuzumab resistance in GC models, providing the rationale for the inhibition of this receptor as a potential second-line strategy in this disease. Pemigatinib is a selective, potent, oral inhibitor of FGFR1, 2, and 3. Methods: The FiGhTeR trial is a phase II, single-arm, open-label study to assess safety and activity of the FGFR inhibitor pemigatinib as second-line treatment strategy in metastatic EGJ/GC patients progressing under trastuzumab-containing therapies. The primary endpoint is the 12-week progression-free survival rate. Plasma and tumor tissue samples will be collected for translational research analyses at baseline, during treatment, and at progression on pemigatinib. Discussion: Co-alterations in genes coding for different tyrosine-kinase receptors are emerging as relevant mechanisms of acquired resistance to anti-HER2 therapeutic strategies in GC. In particular, our group has recently identified that in GC models the overexpression of FGFR3 sustains the acquired resistance to trastuzumab. This trial aims to assess the safety, tolerability and activity of the FGFR inhibitor pemigatinib as a second-line treatment in metastatic EGJ/GC patients refractory to first-line trastuzumab-containing therapies. Furthermore, this study offers the opportunity to prospectively study mechanisms and pathways involved in trastuzumab resistance. Protocol number: CRC2017_02 EudraCT Number: 2017-004522-14